Rethinking Comics and Visuality, from the Audio Daredevil to Philipp Meyer's Life - Brandon Christopher (Disability Studies Quarterly, 2018)
This essay examines two comics that question, either implicitly or explicitly, the near-ubiquitous association of comics and the visual. First, it examines the 'audio edition' of Mark Waid's Daredevil #1, an attempt to translate the comic into an aural medium, and assesses the efficacy of translating a text that has been conceived as visual into a non-visual form. It then turns away from mainstream, visually-conceived comics, examining Philipp Meyer's Life, a 2013 independent comic designed to be read by sighted and non-sighted readers. Taken together, these readings propose that comics' presumed dependence on visuality is more arbitrary than has heretofore been acknowledged.